Molecular changes in aqueous humor associated with inflammation following cataract surgery in patients with fuchs’ endothelial corneal dystrophy - Chychko, Lizaveta; Son, Hyeck Soo; Friedrich, Maximilian; Khoramnia, Ramin; Auffarth, Gerd U.; Augustin, Victor A. (Ophthalmology and therapy, 2025)
To evaluate the anterior chamber (AC) inflammation in the early postoperative period after cataract surgery and before Descemet membrane endothelial keratoplasty (DMEK) by quantifying oxidative stress and inflammatory mediators in aqueous humor of patients with Fuchs’ endothelial corneal dystrophy (FECD).